1989
DOI: 10.1002/smj.4250100708
|View full text |Cite
|
Sign up to set email alerts
|

Top management teams and organizational renewal

Abstract: c Increasingly the makeup of the top management group is believed to affect the development, identification and exploitation of strategic opportunities. This paper explains a creative management model, which goes beyond conventional strategic management, and ident$es the behaviors of top managers needed for the ongoing renewal of their business. It is proposed these behaviors cluster and can be aligned with different and distinct cognitive styles or types. The implication is that top management groups should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(104 citation statements)
references
References 15 publications
2
97
0
2
Order By: Relevance
“…Some arguments support the proposition that greater diversity is likely to bring advantages to the firm due to various reasons. Women are considered to have "feeling" cognitive style that focuses on harmony (Hurst et al, 1989) and ability to facilitate dissemination of information (Earley and Mosakowski, 2000). They are also considered "tough" since they have to face various challenges prior to holding seats on the board, which reward them great prestige in the environment (Krishnan and Park, 2005).…”
Section: Gender Diversitymentioning
confidence: 99%
“…Some arguments support the proposition that greater diversity is likely to bring advantages to the firm due to various reasons. Women are considered to have "feeling" cognitive style that focuses on harmony (Hurst et al, 1989) and ability to facilitate dissemination of information (Earley and Mosakowski, 2000). They are also considered "tough" since they have to face various challenges prior to holding seats on the board, which reward them great prestige in the environment (Krishnan and Park, 2005).…”
Section: Gender Diversitymentioning
confidence: 99%
“…Gender diversity is believed to bring advantages to the organization for the reason that women are considered to have a "feeling" cognitive style (Krishnan and Park, 2005). This type of cognitive style emphasizes on organizational values and harmony (Hurst et al, 1989), encourages sharing of information and resources (Earley and Mosakowski, 2000), facilitates conflict resolution, and shows more democratic leadership (Eagly and Johnson, 1990).…”
Section: Gender Diversitymentioning
confidence: 99%
“…Thus, for the individual member within the organization, climate takes the form of a set of attributes and expectancies that describe the organization in terms of behavior-outcome contingencies (Hershberger, Lichtenstein, & Knox, 1994). The label self-renewal organizational climate is used to refer to the organizational renewal phenomenon whereby the organization seeks to improve its competitive advantage by creating continuously changing atmospheres to set in motion its internal processes, structures, and capabilities (Hurst et al, 1989;McGivem, 1998). Several researchers have concluded that successful corporate renewal overcomes the inertial forces embraced in an organization's established strategies and reduces the mismatches between the evolving basis of competitive advantage facing the organization and its existing core competencies to respond to those conditions (Floyd & Lane, 2000;Huff, Huff, & Thomas, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The term renewal has come to be identified as an intensely social process, involving certain crucial interactions between levels of management (Hurst et al, 1989). This literature suggested that such interactive cooperation is intended to improve individual role performance and to contribute to the organization's adaptability.…”
Section: Interactive Cooperationmentioning
confidence: 99%
See 1 more Smart Citation